Plurality Rule, Proportional Representation, and the German Bundestag: How Incentives to Pork-Barrel Differ Across Electoral Systems - Thomas Stratmann; Martin Baur (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper examines the importance of electoral rules for legislators' behavior. The German electoral system includes a mechanism which assigns whether legislators are elected under the first-past-the-post (FPTP), or the proportional representation (PR) electoral rule. Using this institution, we identify the effect of electoral rules on legislators' behavior and disentangle whether so-called pork barrel politics are due to political climate in a country or due to the electoral rule employed. We find significant differences in committee membership, depending whether the legislator is elected though FPTP or PR. legislators elected through FPTP system are members of committees that allows them to service their geographically based constituency. Legislators elected through PR are members of committees that service the party constituencies, which are not necessarily geographically based.
Keywords: 330